2016
DOI: 10.3390/rs8050426
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Registration Method for Optical Remote Sensing Images with Large Background Variations Using Line Segments

Abstract: Abstract:Image registration is an essential step in the process of image fusion, environment surveillance and change detection. Finding correct feature matches during the registration process proves to be difficult, especially for remote sensing images with large background variations (e.g., images taken pre and post an earthquake or flood). Traditional registration methods based on local intensity probably cannot maintain steady performances, as differences are significant in the same area of the correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…In this section, the performance of the proposed RLI method is evaluated on a series of synthetic and real remote sensing image pairs, and then compared with the performances of RMLSM [31], SIFT [12], MSLD [25] and LP [29]. The parameter setting, data sets, and experimental results are presented as follows.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, the performance of the proposed RLI method is evaluated on a series of synthetic and real remote sensing image pairs, and then compared with the performances of RMLSM [31], SIFT [12], MSLD [25] and LP [29]. The parameter setting, data sets, and experimental results are presented as follows.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…This algorithm can robustly match frontal faces under extreme illuminations; but the vertical symmetry of frontal faces which was used to remove false edges, might not be effective in other scenarios. Shi and Jiang [31] proposed an automatic image registration method that utilized the midpoints of line segments to generate shape context and describe shape contours (named RMLSM for short). The experimental results showed that this method could be used in the registration of remote sensing images with evident background changes.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate its performance, the complete framework is compared with SIFT and other three state-of-the-art matching methods, namely, two matching methods for remote sensing images with background variations (i.e., see Jiang [5] and Shi [20]) and a 2-channel deep network-based method (i.e., see Zagoruyko [19]). The comparative NCM, MP, and RMSE values are shown in Tables 2-4, respectively.…”
Section: Performance Evaluation Of the Proposed Matching Frameworkmentioning
confidence: 99%
“…However, this method does not match with high-resolution remote sensing images because unreliable edge gradient information exists in these kinds of images. A line segment-based method is proposed to match remote sensing images with large background variations [20]. In this method, line segments are extracted by using an edge drawing line (EDLines [20]) detector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation